Optimasi Penyetelan Celah Elektroda Busi Terhadap Emisi Gas Buang Pada Sepeda Motor Matic - Muhamad Zaki; Mulyadi (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2022)
The development of the number of motorized vehicles in Indonesia is increasing rapidly each year, most motorized vehicles produce bad exhaust emissions, either due to inadequate maintenance or bad driver behavior. Air pollution that has occurred so far is largely due to the presence of motorized vehicles as a means of transportation. Most of the air pollution is caused by motor vehicle emissions. Motor vehicles emit harmful gases which can have a negative impact on both human health and the environment. As for the problems that occur that we often encounter, one of them is the process of replacing spark plugs where these spark plugs are part of the engine component, which, if the maintenance process is neglected, will have an impact on exhaust emissions, one of the causes of the process of adjusting the spark plug electrode gap. The process of this research is to design data collection through Experiments with Optimization of Adjustment of the spark plug electrode gap on the matic vario 125 motorcycle vehicle in 2014. Then the results of the adjustment are known to be different from the adjustment of the spark plug gap with lower exhaust emissions of CO and HC levels. This study uses Perthalite type fuel, then adjusts the spark plug gap 0.20 mm, until the adjustment process is 1.40 mm at 900 rpm, 2000 rpm and 2100 rpm rotation, the engine with the aim of knowing the characteristics of the exhaust gas that comes out of the vehicle into the environment . Based on the results of this study where the CO and HC values were the best at setting the spark plug gap of 0.60 mm with CO 1.77% and HC 360 ppm at 900 rpm and CO 0.11% and HC 74 ppm at 2000 rpm and 2100 rpm rotation.